A study on factors associated with abnormal lipid profile of Filipino postmenopausal women - Jocson, Milagros Tia-
OBJECTIVE: To determine the various factors associated with the lipid profile of Filipino postmenopausal women. DESIGN: Cross-sectional study. PARTICIPANTS: 198 postmenopausal women from selected communities / barangays of Metro Manila who were not on HRT nor on any lipid-lowering drugs and not known diabetics were included. Active recruitment was also done at The Medical City. VARIABLES: Duration of postmenopausal period in years, dietary fat intake in terms of percentage of total daily caloric intake, body mass index, waist-hip ratio and level of physical activity were measured and their association with lipid profile - total cholesterol, LDL-c, HDL-c and triglycerides levels - were determined. RESULTS: Diet containing more than 30% of fat is significantly associated with high-risk levels of total cholesterol (adjusted OR 3.92, p=0.21). Physical activity is significantly associated with high-risk cholesterol (adjusted OR 2.19, p=0.03) and clinically but not statistically associated with high-risk LDL-c (adjusted OR 1.89, p=.08) and high risk triglycerides (adjusted OR 3.6, p 0.06). BMI of -/> 25 (overweight and obese), on the other hand, is significantly associated with high-risk triglycerides (adjusted OR 3.56, p=0.01). No association between duration of postmenopausal period nor between body fat distribution (WHR), and lipid profile is noted. CONCLUSION: Lipid profile of postmenopausal women is significantly associated with dietary fat intake, level of physical activity and body mass index.